2018
DOI: 10.1200/jgo.17.00059
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cranial Irradiation for Extensive-Stage Small-Cell Lung Cancer: A Retrospective Analysis

Abstract: PurposeExtensive-stage small-cell lung cancer (esSCLC) is an incurable disease and represents a therapeutic challenge because of its poor prognosis. Studies in prophylactic cranial irradiation (PCI) in esSCLC have shown a decreased incidence of symptomatic brain metastases in patients who respond to systemic chemotherapy. However, its effect on overall survival is debatable. We evaluated the benefit of PCI in patients with esSCLC in terms of overall survival, progression-free survival, incidence of brain metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…If the literature provided the univariate and multivariate analysis results of overall survival, the multivariate analysis results were used because they minimized the influence of confounding factors. Eight [ 7 10 , 18 , 20 , 24 , 25 ] of included studies provided HRs and related 95% CI. HRs were also obtained based on survival curves from five retrospective trials [ 17 , 21 – 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…If the literature provided the univariate and multivariate analysis results of overall survival, the multivariate analysis results were used because they minimized the influence of confounding factors. Eight [ 7 10 , 18 , 20 , 24 , 25 ] of included studies provided HRs and related 95% CI. HRs were also obtained based on survival curves from five retrospective trials [ 17 , 21 – 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 7 , 10 , 18 , 20 , 25 ] reported progression-free survival (PFS) in patients receiving PCI versus control. The random effect model was used as the I 2 was 64%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations